71.6k views
4 votes
Solve 2(5+a)+6(2a-3)

2 Answers

4 votes

Answer:

=14a−8

Explanation:

2(5+a)+6(2a−3)

Distribute:

=(2)(5)+(2)(a)+(6)(2a)+(6)(−3)

=10+2a+12a+−18

Combine Like Terms:

=10+2a+12a+−18

=(2a+12a)+(10+−18)

=14a+−8

Answer:

=14a−8

User Pavel Gatilov
by
5.4k points
4 votes

2(5+a)+6(2a-3)

mutiply the first bracket by 2

(2)(5)= 10

(2)(a)= 2a

mutiply the second bracket by 6

(6)(2a)= 12a

(6)(-3)= -18

10+2a+12a-18

-8+14a or 14a-8

Answer:

-8+14a or 14a-8

User Kris Pruden
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.